Effects of Long-Term Endogenous Corticosteroid Exposure on Brain Volume and Glial Cells in the AdKO Mouse - Amaya, Jorge Miguel; Suidgeest, Ernst; Sahut-Barnola, Isabelle; Dumontet, Typhanie; Montanier, Nathanaëlle; Pagès, Guilhem; Keller, Cécile; van der Weerd, Louise; Pereira, Alberto M.; Martinez, Antoine; Meijer, Onno C. (Frontiers in Neuroscience, 2021)
Chronic exposure to high circulating levels of glucocorticoids has detrimental effects in health, including metabolic abnormalities, as exemplified in Cushing's Syndrome (CS). Magnetic Resonance Imaging (MRI) studies have found volumetric changes in gray and white matter of the brain in CS patients during the course of active disease, but also in remission. In order to explore this further, we performed MRI-based brain volumetric analyses in the AdKO mouse model for CS, that presents its key traits. AdKO mice had reduced relative volumes in several brain regions, including corpus callosum and cortical areas. The medial amygdala, bed nucleus of the stria terminalis and hypothalamus were increased in relative volume. Furthermore, we found lower immunoreactivity of Myelin Basic Protein (MBP, an oligodendrocyte marker) in several brain regions, but a paradoxically increased MBP signal in the male cingular cortex. We also observed a decrease in the expression of GFAP (Glial Fibrillary Acidic Protein, a marker for reactive astrocytes) and IBA1 (Ionized calcium-Binding Adapter molecule 1, a marker for activated microglia) in the cingular regions of the anterior corpus callosum and the hippocampus. We conclude that long term hypercorticosteronemia induced brain region specific changes that might include aberrant myelination, and a degree of white matter damage, as both repair (GFAP) and immune (IBA1) responses are decreased. These findings suggest a cause for the changes observed in the brains of human patients, and serve as a background for further exploration of their subcellular and molecular mechanisms.